THE IMPLEMENTATION OF STAD MODEL TO ENHANCE CIVIC ENGAGEMENT AMONG GRADE V STUDENTS AT SDN BINGIN RUPIT - Miranda (Teaching and General Education Studies, 2025)
This research is motivated by the low involvement of students in the learning process of Pancasila and Citizenship Education (PPKn), especially in various norm materials. Students tend to be passive, lack enthusiasm, and their learning outcomes do not reach the Minimum Completeness Criteria (KKM). Therefore, a learning approach is needed that can increase students' active participation in the learning process. One model that is seen as effective is the Student Teams Achievement Division (STAD), which is a cooperative learning model that emphasizes teamwork and shared responsibility. The purpose of this study is to find out whether the application of the STAD learning model can increase student involvement in PPKn learning in grade V of SDN Bingin Rupit. This study uses a pseudo-experimental method with a One Group Pretest-Posttest design. Data is collected through observation and test instruments. The results showed a significant increase in student engagement after the implementation of the STAD model. The average student engagement score increased from 2.8 to 4.1 (high category). The implementation of STAD also encourages students to be more active in discussing, answering questions, and helping each other in understanding the material. In conclusion, the STAD model is effective in increasing student involvement and understanding in PPKn learning at the elementary school level. It is recommended that the STAD model be applied more broadly in Civic Education and other subjects to enhance collaborative skills and engagement. Future studies could examine its long-term impact on civic attitudes and democratic behavior.